Literature Review: Literasi Digital, Literasi Ekonomi, Dan Inovasi Bisnis Mempengaruhi Manajemen Strategi Pemasaran Usaha Mikro Kecil Menengah - Edi Irawan (Ebisnis Manajemen, 2023)
Based on the results of the discussion, several important things can be concluded, including: First, digital literacy refers to the ability of MSMEs to use digital technology and communication tools via the internet to obtain business materials and share business information widely. The use of digital technology is considered to be able to increase productivity, turnover and income of MSMEs themselves, and is also part of efforts to maintain business continuity. Second, from an economic literacy perspective, micro, small and medium business actors need fundamental knowledge regarding the basic needs of consumers before producing goods or services as well as analyzing the opportunities and challenges of the business or business they are about to start working on. Third, a business venture that is able to innovate will be able to take the lead and reduce the possibility of competitors innovating earlier. Therefore, business people must prepare an innovation strategy for their business ventures in order to create an advantage over competitors. Then continuous innovation in a company is a fundamental need that will be able to create competitive advantages.